Chess players' thinking a cognitive psychological approach - Saariluoma, Pertti (Routledge, 1995)
Chess has always been of interest to cognitive psychologists because it provides a way of investigating processes like thinking, memory, problem solving and the differences between machine and human processes. Chess Players' Thinking presents a new view about experts' thinking and how it should be studied. It provides a comprehensive analysis of chess players' cognition, but its main results should be generalizable to broader research on human expertise. Chess Players' Thinking provides readers interested in human cognitive skills with a new concept-based approach. It introduces and reanalyses a number of classic psychological concepts such as apperception and restructuring. It will be of great interest to all cognitive psychologists and scientists working on human skills.